Coordinate System Alignment Algorithm of Advanced Remote Handling System for Decommissioning of Nuclear Facility - Hyun, Dongjun; Kim, Geun-Ho; Lee, Jong-Hwan; Jeong, Kwan-Seong; Choi, Byung-Seon; Moon, Jeikwon (Asian Journal of Chemistry, 2014)
A novel coordinate system alignment algorithm is proposed for an advanced remote handling system which is the key solution to dismantle heavy, chemically contaminated and highly radioactive components during nuclear facility decommissioning. A high radiation field and chemical contamination extremely limit hands-on operations by workers for safety and radiation protection and a heavy component requires high payload capacity and long lead-time for dismantling operations, which are not suitable for human workers. Over the last decades, several remote handling systems have been developed to dismantle highly activated heavy components in nuclear facility decommissioning and have achieved specific goals. However, the well-known disadvantages of the remote operation, which are a limited cognition and the complex operation, still obstructs the expanding application of a remote handling system. The algorithm in this paper presents an original methodology using the polar scan matching algorithm and the multi-rate extended Kalman filtering algorithm to align coordinate systems of the known 3D digital model and 3D scanning data over the remote workshop in a remote handling system composed of systems having different operational periods and can largely contribute to an advanced remote handling system with a user friendly interface.